Soft spot: the important zone at the standard posterior portal of shoulder arthroscopy - Ercakmak, Burcu; Gunenc Beser, Ceren; Ozsoy, M. Hakan; Demiryurek, M. Deniz; Bayramoglu, Alp; Hayran, K. Mutlu (TUBITAK SCIENTIFIC \& TECHNICAL RESEARCH COUNCIL TURKEY, 2018)
Background/aim: The localization of the standard posterior portal of shoulder arthroscopy and landmarks mentioned in the literature are unclear. The purpose of this prospective cadaveric study was to determine the localization of the standard posterior portal and its distance to the neural structures. Materials and methods: One fresh frozen and 10 formalin-fixed adult cadaveric shoulders were dissected. In the beach chair position, a 5-mm trocar was placed anteroposteriorly from the superior edge of the subscapularis muscle, superior to the tip of the coracoid process and tangent to the glenoid. The relevant distances of the posterior exit point were measured. Results: In all specimens, the exit point was a triangular fibrous area, between the posterior and lateral parts of the deltoid. Medial and inferior distances of the trocar to the posterolateral tip of the acromion were 1.88 +/- 0.53 cm and 1.35 +/- 0.34 cm and distances to the axillary and suprascapular nerves were 4.54 +/- 1.08 cm and 2.54 +/- 0.85 cm, respectively. Conclusion: The most important finding of this study was the superficial localization of the soft spot between the posterior and lateral parts of deltoid.
Keywords: Shoulder arthroscopy; posterior portal; soft spot; anatomy